A Review of Potentially Toxic Elements in Sediment, Water, and Aquatic Species from the River Ecosystems - Md Muzammel Hossain; Iffat Jahan; Mudasir A. Dar; Maruti J. Dhanavade; Al Fattah Bin Mamtaz; Stephen J. Maxwell; Song Han; Daochen Zhu (Toxics)
There is concern over potential toxic elements (PTEs) impacting river ecosystems due to human and industrial activities. The river’s water, sediment, and aquatic life are all severely affected by the release of chemical and urban waste. PTE concentrations in sediment, water, and aquatic species from river ecosystems are reported in this review. Among the PTEs, chromium (Cr), cadmium (Cd), lead (Pb), and nickel (Ni) revealed high pollution levels in water and aquatic species (fish and shellfish) at many rivers. The Karnaphuli, Ganga, and Lee rivers have high levels of Pb and Cd contamination, while the Buriganga and Korotoa rivers’ water had notable Ni contamination. A number of rivers with PTEs showed ecological risk as a consequence of the sediment’s potential ecological risk (PER), the pollutant load index (PLI), and the geoaccumulation index (Igeo). A comprehensive study suggests elevated PLI values in river sediments, indicating significant pollution levels, particularly in the Buriganga River sediment, marked by high Igeo values. The PER of the Shitalakshya and Buriganga rivers was marked as very high risk, with an Eir > 320, while the Dhaleshwari and Khiru rivers showed ‘high risk’, with 160 = Eir < 320. It was found that fish and shellfish from the Buriganga, Turag, and Swat rivers have a high concentration of Cr. PTE pollution across several river sites could pose health toxicity risks to humans through the consumption of aquatic species. The CR value shows the carcinogenic risk to human health from eating fish and shellfish, whereas an HI value > 1 suggests no carcinogenic risk. The occurrence of other PTEs, including manganese (Mn), arsenic (As), and nickel (Ni), significantly increases the ecological risk and concerns to aquatic life and human health. This study emphasises the importance of PTE toxicity risk and continuous monitoring for the sustainability of river ecosystems.